Microalloying as a key strategy to maximize the strength–ductility combination in dilute titanium alloys - P. Kwasniak; S. Delannoy; P. Vermaut; F. Sun; M.R. Zemła; T. Zakharava; F. Prima (Materials Research Letters, 2025)
A highly effective microalloying strategy for titanium hardening is presented. The main idea of this approach is to activate a novel strengthening mechanism, i.e. precipitation strengthening with nanoscale β particles located inside the α matrix. Such microstructures together with substantial grain refinement observed in the model, recrystallized Ti–Re alloys result in a 2.8 times increase in yield strength, relative to pure Ti and a high ∼35% elongation obtained at 0.5 wt.% (0.13 at.%) Re content. It is expected that similar properties can be obtained using other strong beta-stabilizers, making this method a universal way to improve the mechanical properties of Ti-based materials.